PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KELOMPOK TANI IMMANUEL DI DESA RARINGIS KECAMATAN LANGOWAN BARAT KABUPATEN MINAHASA - WAWORUNTU, FRISCA; LENGKONG, FLORENCE; LONDA, VERY (Sam Ratulangi University, 2021)
ABSTRACKIn this increasingly developing era, a nation is required to be able to design sustainable developmentstrategies in advancing its nation. This development can be in the form of physical development or otherresources, community empowerment as one of the methods or methods that can be used in the grandframework of national development. The purpose of this study was to determine CommunityEmpowerment through the Immanuel Farmer Group Program in Raringis Village, West LangowanDistrict, Minahasa Regency. The theory used in this study is the theory of Community Empowerment fromSumodiningrat (2007) which contains three stages of empowerment, namely the stage of awareness andbehavior formation, the stage of transformation of work abilities, and the stage of increasing intellectualabilities. This study uses descriptive qualitative research, namely to obtain more complete, more in-depth,credible and meaningful data by conducting interviews with 8 informants and also by collectingdocuments related to community empowerment so that the objectives of the research will be achieved. Theresults of this study describe community empowerment through the Immanuel farmer group program inRaringis Village, West Langowan District, Minahasa Regency, it has been going quite well in terms of theapplication of the three indicators of the empowerment stage.